Skin Necrosis Associated with Thromboprophylaxis after Total Knee Replacement - S. V. Karuppiah; A. J. Johnstone (Case Reports in Orthopedics)
Thromboprophylaxis are routinely given to prevent venous thromboembolism (VTE) in patients after total hip and knee replacement surgeries. Low molecular weight heparin (LMWH) (fractioned heparin) is effective in the prevention and treatment of VTE. The predicable effect of LMWH has popularized it for routine clinical use. Although LMWH has lesser complication rate, compared to unfractioned heparin (UFH), sporadic clinical complication has been reported. We report a rare case of skin necrosis secondary to use of LMWH tinzaparin used for routine thromboprophylaxis after total knee replacement.